THE PAST AND THE PRESENT OF THE CONSTITUTIONAL SYSTEMS OF THE REPUBLIC OF MACEDONIA IN TERMS OF THE POSITION OF ALBANIANS - Shasivari, Jeton (European Scientific Journal, ESJ, 2013)
In this paper, the author analyzes the legal, political and historical aspects of constitutional systems of the Republic of Macedonia in terms of the position of Albanians, within the three time periods, respectively the first period which includes the socialist regime (1946-1990), the second period which includes the period after the country became independent in 1991 up to the armed conflict of 2001 and the third period which includes the period after the armed conflict of 2001 until today.